2012
DOI: 10.1007/s00068-012-0236-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of current treatment regimens for prepatellar and olecranon bursitis in Switzerland

Abstract: Purpose Bursitis is a common entity. However, evidence for the best treatment procedures is lacking, with management concepts varying internationally. We evaluated current treatment regimens for septic (SB) and nonseptic (NSB) prepatellar (PB) and (OB) olecranon bursitis in Switzerland and compared them to the published literature. Methods A voluntary 23-item online survey was distributed amongst all registered Swiss infectiologists and orthopedic surgeons in December 2011. The literature comparison was based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This methodology also may have resulted in the misclassification of some patients as septic when they were truly aseptic. However, due to the inherent limitations of medical records, we felt that this was the best available method to distinguish septic from aseptic bursitis and is supported by the findings of Baumbach et al [25]. Furthermore, our sample size was limited due to this study requiring preoperative and postoperative patient-reported outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…This methodology also may have resulted in the misclassification of some patients as septic when they were truly aseptic. However, due to the inherent limitations of medical records, we felt that this was the best available method to distinguish septic from aseptic bursitis and is supported by the findings of Baumbach et al [25]. Furthermore, our sample size was limited due to this study requiring preoperative and postoperative patient-reported outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…The optimal duration of postoperative antibiotics remains uncertain. In a study by Baumbach et al (2013a) surveying Swiss infectious diseases and orthopedic surgeons regarding the management of septic bursitis, a range of postoperative antibiotic durations were reported, varying between 3 and 28 d. Moreover, 25 of the 92 (27 %) surveyed physicians did not routinely prescribe antibiotics postoperatively (Baumbach et al, 2013a). In our cohort, excluding initial bacteremia or osteomyelitis, the median postoperative antibiotic course was 21 d, although with wide variability in both the route and duration of antibiotic treatment, ranging from 0 to 102 d. In a study by Perez et al (2010), a short antibiotic course (≤ 7 d) following bursectomy for olecranon or prepatellar septic bursitis in immunocompetent patients was not associated with an increased risk of infection relapse compared with longer courses (8-14 or > 14 d).…”
Section: Discussionmentioning
confidence: 98%
“…Surgery is typically reserved for select cases such as those involving refractory or relapsing infection, critically ill patients, presence of extensive peribursal soft tissue involvement requiring debridement, presence of a bursal abscess that fails needle aspiration, or for patients with chronic draining sinus (Baumbach et al, 2014;Small and Ross, 2005;Zimmermann et al, 1995). The ideal surgical approach (incision and drainage vs. bursectomy) remains debated (Lormeau et al, 2019;Baumbach et al, 2013a). In patients undergoing bursectomy, a one-stage procedure was effective, safe, and associated with lower rates of wound dehiscence compared with the two-stage approach (Uçkay et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baumbach et al [7] documented 36 different treatment modalities for bursitis in Switzerland alone in 2013. Treatment is commonly divided by aetiology, separating septic and aseptic bursitis, with most cases amenable to non-operative treatment.…”
Section: Introductionmentioning
confidence: 99%